TURNOVER INTENTION SERVICES COMPANIES: A SYSTEMATIC REVIEW - Halimaton Sa’adiah Abdul Jalil; Amelia Mohd Noor; Aslina Ahmad (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Turnover intention is a significant problem most service companies are facing, as it can directly affect employee retention, organisational performance, and general productivity of the companies that provide service. This scholarly review analyses the systematic review factors impacting turnover intention, organized around four major themes: (1) Organisational Commitment and Turnover Intention, (2) Work-Related Stimuli and Psychological Sources, (3) Human Resource (HR) Industry and Job Satisfaction and Retention strategies, (4) Miscellaneous or Inter-Thematic research. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, we performed a systematic search for academic articles published between the years 2021 and 2024 in Scopus and ERIC databases. A systematic review of the current primary literature was performed, resulting in 35 studies grouped according to certain inclusion criteria. These were then used to identify emerging trends and highlights of the field. This positively affects turnover intention and highlights the significance of organisational commitment and best practices of HR for turnover intention.